Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1161/01.cir.103.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type 2 Diabetes Mellitus on Left Ventricular Geometry and Systolic Function in Hypertensive Subjects

Abstract: In a relatively healthy, population-based sample of hypertensive adults, type 2 diabetes was associated with higher LV mass, more concentric LV geometry, and lower myocardial function, independent of age, sex, body size, and arterial BP. structural and functional abnormalities in addition to, and independent of, atherosclerosis.(13) (14) In the Framingham cohort, diabetes was associated with higher LV mass in women but not men.(15) High blood pressure (BP), obesity, and abnormal lipid profile, which often coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
175
6
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(222 citation statements)
references
References 57 publications
25
175
6
8
Order By: Relevance
“…29 In the Strong Heart Study, 27 which involved a wide group of American Indians, diabetic subjects had higher LVM, interventricular septum thickness, PWT and RWT in comparison with subjects without diabetes, with no difference in LV chamber size. Similar results were obtained in the HYperGEN Study, 28 in which diabetic hypertensives had higher LVM and more concentric geometry when compared with non-diabetic hypertensives (again in this study diabetics had higher LVM, interventricular septum thickness, PWT and RWT but there was no difference with regard to LV diameter). However, in this study the relation of diabetes with LVH lost statistical significance when duration of hypertension was included in the statistical analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…29 In the Strong Heart Study, 27 which involved a wide group of American Indians, diabetic subjects had higher LVM, interventricular septum thickness, PWT and RWT in comparison with subjects without diabetes, with no difference in LV chamber size. Similar results were obtained in the HYperGEN Study, 28 in which diabetic hypertensives had higher LVM and more concentric geometry when compared with non-diabetic hypertensives (again in this study diabetics had higher LVM, interventricular septum thickness, PWT and RWT but there was no difference with regard to LV diameter). However, in this study the relation of diabetes with LVH lost statistical significance when duration of hypertension was included in the statistical analysis.…”
Section: Discussionsupporting
confidence: 88%
“…27,28 Moreover, diabetes has a negative impact on treatment-induced changes in LV structure and function in hypertensives with LVH. 29 In the Strong Heart Study, 27 which involved a wide group of American Indians, diabetic subjects had higher LVM, interventricular septum thickness, PWT and RWT in comparison with subjects without diabetes, with no difference in LV chamber size.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,9 Non-insulin-dependent diabetes mellitus has been independently associated with an increase in left ventricular mass. 33,34 In our previous study among DHCCP patients, blood glucose concentration tended to be inversely related to the presence of ECG LVH by Sokolow-Lyon criterion. 35 In the Framingham Heart Study after adjusting for BMI and other risk factors, severity of hyperglycaemia was observed to be related to left ventricular mass more strongly in women than in men.…”
Section: Discussionmentioning
confidence: 80%
“…In the 1980s, although controlled prospective studies on the effectiveness and safety of treatment of SBP were lacking, the recommendations on antihypertensive treatment were based on DBP. 33 As most patients referred with hypertension between 1971 and 1986 presented with elevated DBP, this study clearly was biased towards diastolic hypertension. Long-term mortality data were obtained from death certificates, known for their potential inaccuracies.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…All subjects were free from concomitant overt cardiovascular disease and diabetes mellitus, which may have an independent influence on LV mass and function. 21 We also excluded the potential confounding effect of current or previous antihypertensive treatment.…”
Section: Present Studymentioning
confidence: 99%